Air‐Stable, Dinuclear and Tetranuclear σ, π‐Acetylide Gold(I) Complexes and Their Catalytic Implications. Issue 37 (9th August 2013) - Grirrane, Abdessamad; Garcia, Hermenegildo; Corma, Avelino; Álvarez, Eleuterio
<x xml:space="preserve">Abstract</x> Two for one gold: Factors governing the formation of isolable digold(I) σ, π‐acetylide complexes are given (see scheme), indicating the general tendency of phosphine–AuI precatalysts to form this type of complexes, which are involved as reaction intermediates in gold(I)‐catalyzed reactions. Mechanistic insights into the intermolecular hydroamination of aniline and terminal alkynes catalyzed by gold(I) have shown the role of a fluxional, cationic σ, π‐digold alkynide complex as one of the intermediates in the formation of imines.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>